Soil fertility in a city garden on the banks of the Inhangapi River and the qualitative impacts on the water body - Pinheiro, Valdeci Júnior Fonseca; Cardoso, Diego Fabricío Santa Rosa; Silva, Emerson Renato Maciel da; Barbosa, Ivan Carlos da Costa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Soil quality provides essential functions for life and fertility related to minimal damage to the ecosystem, sustains a permanent agricultural activity. This work aims to investigate the physical-chemical quality of the soil in the municipal garden of Inhangapi, in the state of Pará, and possible qualitative changes in a stretch of the Inhangapi River. Sampling was carried out in periods of different rainfall patterns according to the National Institute of Meteorology, in order to identify the influence of rainfall on the evaluated parameters. Subsequently, physical-chemical analyzes were performed at the Laboratory of the Agricultural Technology Center located at the Federal Rural University of the Amazon. With the physical-chemical analyzes of the soil it was verified that there is a need for conservationist practices that aim to improve the cultivation area, through liming, consortium with legumes for better nitrogen supply and maintaining the soil cover to avoid erosion and leaching and use of composting in order to improve the supply of organic matter and improve water retention, since the soil is sandy. The rapid water body assessment protocol was also applied to a stretch of the river. Greater care is needed on the stretch of river where the protocol was applied, such as the use of riparian forest to help with the silting up of the river bed, resulting in water protection in the surrounding area.